2006
DOI: 10.4321/s0365-66912006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la capa de fibras nerviosas de la retina en el estrabismo infantil

Abstract: Objective: To assess possible differences in the retinal nerve fiber layer (RNFL) thickness between children with strabismus and controls. This study also compared esotropia with exotropia cases, and dominant eyes with non-dominant eyes. Method: 31 children with esotropia, 17 children with exotropia and 32 controls were studied. The peripapillary RNFL average thickness was determined in 4 different areas (inferior, superior, nasal and temporal) using optical coherence tomography. Statistical analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Reche-Sainz JA et al [ 32 ] also showed that no statistically significant differences in RNFL thickness were found in any of these statistical comparisons using optical coherence tomography. They evaluated possible differences among children with strabismus and 32 controls, 31 esotropia, and 17 exotropia cases, and comparisons between dominant eyes and non-dominant eyes.…”
Section: Discussionmentioning
confidence: 96%
“…Reche-Sainz JA et al [ 32 ] also showed that no statistically significant differences in RNFL thickness were found in any of these statistical comparisons using optical coherence tomography. They evaluated possible differences among children with strabismus and 32 controls, 31 esotropia, and 17 exotropia cases, and comparisons between dominant eyes and non-dominant eyes.…”
Section: Discussionmentioning
confidence: 96%
“…El estrabismo infantil está siendo también sujeto de la aplicación de OCT en la consulta como se desprende del trabajo presentado por los doctores Reche-Sainz et al en Archivos este mismo año (2).…”
unclassified